MODEL INTEGRATIF MANAJEMEN KEPEMIMPINAN PENDIDIKAN DALAM PENGUATAN KARAKTER DAN KOMPETENSI SISWA SMK DARUSSALAM CILACAP - Siswadi (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2024)
This study aims to examine and develop an integrative model of educational leadership management in strengthening students’ character and competencies at SMK Darussalam Cilacap. The background of this research is based on the dynamic changes in education in the era of disruption, which demand leadership that is not only oriented toward academic achievement but also toward holistic character building and competency development of students. This research employs a qualitative approach with a case study design. Data were collected through observation, in-depth interviews, and documentation, and were analyzed using data reduction, data display, and conclusion drawing, with triangulation techniques applied to ensure data validity. The results indicate that the integrative leadership model implemented at SMK Darussalam Cilacap combines transformational, spiritual, and data-driven leadership dimensions. This leadership approach is capable of fostering a character-based school culture while simultaneously enhancing students’ competencies through industry-based and technology-integrated learning approaches. The model has proven effective in improving students’ discipline, responsibility, and vocational skills. Therefore, this integrative model serves as a strategic alternative for developing adaptive and sustainable educational leadership.